Role of TRPC3 and TRPC6 channels in the myocardial response to stretch: Linking physiology and pathophysiology. (November 2017) - Yamaguchi, Yohei; Iribe, Gentaro; Nishida, Motohiro; Naruse, Keiji
Abstract: Transient receptor potential (TRP) channels constitute a large family of versatile multi-signal transducers. In particular, TRP canonical (TRPC) channels are known as receptor-operated, non-selective cation channels. TRPC3 and TRPC6, two members in the TRPC family, are highly expressed in the heart, and participate in the pathogenesis of cardiac hypertrophy and heart failure as a pathological response to chronic mechanical stress. In the pathological response, myocardial stretch increases intracellular Ca 2+ levels and activates nuclear factor of activated T cells to induce cardiac hypertrophy. Recent studies have revealed that TRPC3 and TRPC6 also contribute to the physiological stretch-induced slow force response (SFR), a slow increase in the Ca 2+ transient and twitch force during stretch. In the physiological response, a stretch-induced increase in intracellular Ca 2+ mediated by TRPC3 and TRPC6 causes the SFR. We here overview experimental evidence of the involvement of TRPC3 and TRPC6 in cardiac physiology and pathophysiology in response to stretch.